CAMPUS FUN RUN MARKS END OF SOM SILVER JUBILEE CELEBRATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 Universiti Sains Malaysia (USM) Campus Fun Run 2015 which will be held on 10 October 2015 will mark the climax of the School of Management (SOM) Silver Jubilee Celebrations.